Social inequality in shadow education: The role of high-stakes testing. (December 2020) - Zwier, Dieuwke; Geven, Sara; van de Werfhorst, Herman G.
Against the background of the worldwide expansion of shadow education, research shows that students from high socio-economic status (SES) backgrounds participate more in shadow education than students from disadvantaged SES backgrounds. We relate these social inequalities in shadow education participation to institutional features of educational systems. More specifically, we argue that the effect of socio-economic background on participation in shadow education will be stronger in countries characterized by high-stakes testing. Using data from the Programme for International Student Assessment for the year 2012 (PISA 2012), we show that higher SES students participate more in shadow education. For three out of four indicators of shadow education, this relationship is stronger in countries that are characterized by high-stakes testing but only when accounting for unobserved country differences.